Voice Against Subjugation of Non-Human World in Hemingway’s The Old Man and the Sea - Lamichhane, Hari Krishna (Rural Development Journal, 2017)
This article on Ernest Hemingway’s novella, The Old Man and the Sea, explores Hemingway’s worries about subjugation of non-human world due to anthropocentric hubris of human beings encroaching and exploiting nature in the modern society. In the novella, he presents the selfishness of the human world where people mercilessly go on fishing in the sea considering the act of killing fish as ‘heroic deed’. The article applies eco-critical insights to study consequences of human encroachment upon nature in the novella. It mainly borrows ideas from Paul W. Taylor’s “Respect of Nature”, Val Plumwood’s “The Blindspots of Centricism and Human Self[1]enclosure” and Arne Naess’ “Deep Ecological Movement: Some Philosophical Aspects”. The article shows Hemingway’s critique of nature exploitation and his appeal for the need of love for nature that he does through his choice of the protagonist, Santiago, and the big marlin who have a combat that Santiago wins after struggling for a long time, but gets defeated by the sharks ultimately. Hemingway, by presenting the protagonist Santiago’s situation, appeals all human beings to love nature.